If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2+u)-u=6+u(u+1)
We move all terms to the left:
3(2+u)-u-(6+u(u+1))=0
We add all the numbers together, and all the variables
3(u+2)-u-(6+u(u+1))=0
We add all the numbers together, and all the variables
-1u+3(u+2)-(6+u(u+1))=0
We multiply parentheses
-1u+3u-(6+u(u+1))+6=0
We calculate terms in parentheses: -(6+u(u+1)), so:We add all the numbers together, and all the variables
6+u(u+1)
determiningTheFunctionDomain u(u+1)+6
We multiply parentheses
u^2+u+6
Back to the equation:
-(u^2+u+6)
2u-(u^2+u+6)+6=0
We get rid of parentheses
-u^2+2u-u-6+6=0
We add all the numbers together, and all the variables
-1u^2+u=0
a = -1; b = 1; c = 0;
Δ = b2-4ac
Δ = 12-4·(-1)·0
Δ = 1
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{1}=1$$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-1}{2*-1}=\frac{-2}{-2} =1 $$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+1}{2*-1}=\frac{0}{-2} =0 $
| 6=2a-2 | | x+4+2x-6=90 | | 100=-5q–5q–10 | | 6(v+5)=-2(5v-8)+6v | | 7x+11-5x-25=-6 | | 7x+12=2x-3 | | 2(6+y)-5y=21 | | 7(x-3)=15+5 | | d22=60 | | 2(6+y)–5y=21 | | (2x+15)+61=180 | | 4y+2=6y-20 | | 9w-8+2(2w+2)=-2(w+7) | | 2x+1=3x+13 | | 4.50.25a+0.5=4.5 | | 2x+1=3×+13 | | -21=s-17 | | -2r=-r+11 | | 6(y+3)+3=9 | | 10(x−1)=5(x+2) | | 8h-12=6h | | 3x+9=8x+14 | | t-10/4=-4 | | 17+w=19 | | t–104=-4 | | -5a+10a=10 | | -4=2(s+5) | | 1=-6z+5z | | 5(x+3)–3x=55 | | 69=-391+4x | | 18=7r+18 | | 2(y-6)+3=2y-7 |